Pengaruh Stress Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Dengan Cyberloafing Sebagai Variable Intervening - Siska Nuria Fita (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
The purpose of this study was to find out how much influence work stress (X1), workload (X2) have on cyberloafing (Y1) and employee performance (Y2). This study uses an explanatory research approach with quantitative methods. Collecting data in this study is by distributing questionnaires to 100 respondents. Data analysis techniques use SPSS software version 16, where data will be processed, described and discussed to answer and prove the hypotheses proposed. The research results are as follows: (1). Job Stress (X1) has a positive and significant effect on Cyberloafing behavior (Y1). (2). Workload (X2) has a positive and significant effect on Cyberloafing Behavior (Y1). (3). Job stress has a positive and significant effect on employee performance (Y2). (4). Workload (X2) has a negative and insignificant effect on employee performance (Y2). (5) Cyberloafing behavior (Y1) has a positive and significant effect on employee performance (Y2).